Courses
Courses for Kids
Free study material
Offline Centres
More
Store

# Let the arithmetic & geometric mean of two numbers be $A$ and $G$ respectively, then prove that the numbers are $A \pm \sqrt {\left( {A + G} \right)\left( {A - G} \right)}$.

Last updated date: 15th Jul 2024
Total views: 449.1k
Views today: 13.49k
Verified
449.1k+ views
Hint: Take any two variables, find their A.M (Arithmetic Mean) and G.M (Geometric Mean) accordingly and then simplify them.

Let $x$ and $y$ be the two numbers whose A.M is $A$ and G.M is $G$ respectively
i.e. $x = A + \sqrt {\left( {A + G} \right)\left( {A - G} \right)}$
$y = A - \sqrt {\left( {A + G} \right)\left( {A - G} \right)}$

where $A = \dfrac{{x + y}}{2}$ and $G = \sqrt {xy}$

Now solving $A \pm \sqrt {\left( {A + G} \right)\left( {A - G} \right)}$
$= \left( {\dfrac{{x + y}}{2}} \right) \pm \sqrt {{{\left( {\dfrac{{x + y}}{{\text{2}}}} \right)}^2} - {{\left( {\sqrt {xy} } \right)}^2}}$
Expanding terms inside the square root
$\\ = \left( {\dfrac{{x + y}}{2}} \right) \pm \sqrt {\left( {\dfrac{{{x^2} + {y^2} + 2xy}}{4}} \right) - \left( {xy} \right)} \\ = \left( {\dfrac{{x + y}}{2}} \right) \pm \sqrt {\dfrac{{{x^2} + {y^2} + 2xy - 4xy}}{4}} \\ = \left( {\dfrac{{x + y}}{{\text{2}}}} \right) \pm \sqrt {\dfrac{{{x^2} + {y^2} - 2xy}}{4}} \\ = \left( {\dfrac{{x + y}}{{\text{2}}}} \right) \pm \sqrt {{{\left( {\dfrac{{x - y}}{{\text{2}}}} \right)}^2}} \\ = \left( {\dfrac{{x + y}}{2}} \right) \pm \left( {\dfrac{{x - y}}{{\text{2}}}} \right) \\$
First let’s consider the positive sign, we get
$= \left( {\dfrac{{x + y}}{{\text{2}}}} \right) + \left( {\dfrac{{x - y}}{{\text{2}}}} \right) \\ = \dfrac{x}{2} + \dfrac{y}{2} + \dfrac{x}{2} - \dfrac{y}{2} \\ = \dfrac{x}{2} + \dfrac{x}{2} \\ = x \\$
Now let’s consider the negative sign, we get
$= \left( {\dfrac{{x + y}}{{\text{2}}}} \right) - \left( {\dfrac{{x - y}}{{\text{2}}}} \right) \\ = \dfrac{x}{2} + \dfrac{y}{2} - \dfrac{x}{2} + \dfrac{y}{2} \\ = \dfrac{y}{2} + \dfrac{y}{2} \\ = y \\$
Thus, $x = A + \sqrt {\left( {A + G} \right)(A - G)}$
$y = A - \sqrt {\left( {A + G} \right)(A - G)}$
Hence proved.

Note: In these types of problems, assume required variables to arrive at the solution. Always remember that the Arithmetic Mean of a list of non-negative real numbers is greater than or equal to the Geometric Mean of the same list i.e. $\dfrac{{x + y}}{{\text{2}}} \geqslant \sqrt {xy}$.